Encapsulation efficiency of CdSe/ZnS quantum dots by liposomes determined by thermal lens microscopy - Batalla, Jessica (Biomed Opt Express, 2015)
In this study the encapsulation of core shell carboxyl CdSe/ZnS quantum dots (QDs) by phospholipids liposome complexes is presented. It makes the quantum dots water soluble and photo-stable. Fluorescence self-quenching of the QDs inside the liposomes was observed. Therefore, the thermal lens microscopy (TLM) was found to be an useful tool for measuring the encapsulation efficiency of the QDs by the liposomes, for which an optimum value of 36% was determined. The obtained limit of detection (LOD) for determining QDs concentration by TLM was 0.13 nM. Moreover, the encapsulated QDs showed no prominent cytotoxicity toward Breast cancer cells line MDA-MB-231. This study was supported by UV-visible spectroscopy, high resolution transmission electron microscopy (HRTEM) and dynamic light scattering measurements (DLS).